Kurarinone ameliorates intestinal mucosal inflammation via regulating T cell immunity - Pan, Yan; Deng, Bolin; Wang, Tingting; Zhou, Zhou; Wang, Jinxia; Gao, Caiping; He, Chong (Frontiers in Immunology, 2025)
BackgroundInflammatory bowel disease (IBD) has become an increasingly significant global health concern, imposing substantial economic and psychological burdens on society and public health systems. Herbal medicines, which have shown promise in alleviating IBD symptoms and promoting remission through mechanisms such as immune regulation and anti-inflammatory effects, are gaining increasing attention. Kurarinone (KAR) is a major component of the dried roots of Sophora flavescens, which exhibits a range of pharmacological activities, including antioxidant and anti-inflammatory effects. However, research on the therapeutic potential of KAR in IBD, particularly its effect on intestinal mucosal inflammation, remains limited.MethodsColitis was induced by trinitrobenzene sulfonic acid (TNBS) in mice and KAR was intraperitoneally given. Hematoxylin and eosin staining, flow cytometry, and immunofluorescence were used for mucosal inflammation evaluation. Changes in gut microbiota were assessed using 16S rRNA sequencing. RNA sequencing was performed to screen for KAR’s therapeutic targets, which was verified by in vitro T cell culture.ResultsWe demonstrated that administration of KAR resulted in a mitigated colonic tissue damage in mice with TNBS-induced colitis and decreased the infiltration of inflammatory cells, including monocytes/macrophages, neutrophils, and T lymphocytes. Moreover, KAR protected TNBS-insulted mice from colonic goblet cell loss and tight junction destruction. Furthermore, KAR treatment led to the restoration of the gut microbiota to a more normal composition. Mechanistically, KAR suppressed T helper (Th) 17 cell response but facilitated interleukin (IL)-10 production via Blimp-1.ConclusionOur study investigated the impact of KAR on mice with TNBS-induced colitis and elucidated its underlying mechanisms, thereby uncovering novel possibilities for clinical interventions in IBD.